2015
DOI: 10.1007/s12160-014-9685-9
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as Treatment for Anxiety: Systematic Review and Analysis

Abstract: Background Exercise has been shown to reduce symptoms of anxiety, but few studies have studied exercise in individuals pre-selected because of their high anxiety. Purpose To review and critically evaluate studies of exercise training in adults with either high levels of anxiety or an anxiety disorder. Methods We conducted a systematic review of randomized clinical trials (RCTs) in which anxious adults were randomized to an exercise or non-exercise control condition. Data were extracted concerning anxiety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
182
0
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(213 citation statements)
references
References 107 publications
13
182
0
18
Order By: Relevance
“…In adults with SRVI and SRNI, after adjusting for possible confounders, cross-sectional and prospective analyses revealed no significant associations of leisure-time PA with anxiety symptoms. Most randomized controlled trials (RCTs) of adult populations have found that exercise is associated with fewer anxiety symptoms (Herring et al, 2010;Stonerock et al, 2015), whereas mixed results have been shown in observational studies with prospective designs . However, observational studies are less suitable than RCTs to address cause and effect because the temporal relationship between PA and anxiety symptoms is less clear.…”
Section: Physical Activity and Anxiety Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults with SRVI and SRNI, after adjusting for possible confounders, cross-sectional and prospective analyses revealed no significant associations of leisure-time PA with anxiety symptoms. Most randomized controlled trials (RCTs) of adult populations have found that exercise is associated with fewer anxiety symptoms (Herring et al, 2010;Stonerock et al, 2015), whereas mixed results have been shown in observational studies with prospective designs . However, observational studies are less suitable than RCTs to address cause and effect because the temporal relationship between PA and anxiety symptoms is less clear.…”
Section: Physical Activity and Anxiety Symptomsmentioning
confidence: 99%
“…However, observational studies are less suitable than RCTs to address cause and effect because the temporal relationship between PA and anxiety symptoms is less clear. Nevertheless, as stated in a systematic review, there is not enough evidence yet to support a direct effect of PA on anxiety symptoms (Stonerock et al, 2015). 14 …”
Section: Physical Activity and Anxiety Symptomsmentioning
confidence: 99%
“…Pain ailments occurred more rarely and with lower intensity in the patients with well-controlled blood pressure. Physical activity helps to treat depression and anxiety disorders by enhancing classical pharmacotherapy; however there are very few prospective studies discussing the issue [21]. The haDS scale proves a reliable tool to assess anxiety and depression in chronic diseases [22].…”
Section: Resultsmentioning
confidence: 99%
“…For example, there is consistent evidence that individuals with greater anxiety tend to be less active [10]. It is plausible to suggest that individuals with high levels of anxiety lose motivation due to the consequences associated with anxiety.…”
Section: Introductionmentioning
confidence: 99%